2021
DOI: 10.3390/microorganisms9102087
|View full text |Cite
|
Sign up to set email alerts
|

Voriconazole Pharmacokinetics Are Not Altered in Critically Ill Patients with Acute-on-Chronic Liver Failure and Continuous Renal Replacement Therapy: An Observational Study

Abstract: Infection and sepsis are a main cause of acute-on-chronic liver failure (ACLF). Besides bacteria, molds play a role. Voriconazole (VRC) is recommended but its pharmacokinetics (PK) may be altered by ACLF. Because ACLF patients often suffer from concomitant acute renal failure, we studied the PK of VRC in patients receiving continuous renal replacement therapy (RRT) with ACLF and compared it to PK of VRC in critically ill patients with RRT without concomitant liver failure (NLF). In this prospective cohort stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 41 publications
(63 reference statements)
0
5
0
Order By: Relevance
“…When we look at treatment with an initial dose of 3 mg/kg/12 h of VRC on the first day and a maintenance dose of 2 mg/kg/12 h on each subsequent day, which represent a 50% reduction compared to standard treatment [ 8 , 32 ], we observed behavior similar to that of the standard dose. However, there is a decrease from the PTA for free CSF concentrations, from an MIC of 2 mg/L in the healthy group and an MIC of 4 mg/L in the infected group, and when we look at the exposures in the brain and plasma, they are less successful.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…When we look at treatment with an initial dose of 3 mg/kg/12 h of VRC on the first day and a maintenance dose of 2 mg/kg/12 h on each subsequent day, which represent a 50% reduction compared to standard treatment [ 8 , 32 ], we observed behavior similar to that of the standard dose. However, there is a decrease from the PTA for free CSF concentrations, from an MIC of 2 mg/L in the healthy group and an MIC of 4 mg/L in the infected group, and when we look at the exposures in the brain and plasma, they are less successful.…”
Section: Resultsmentioning
confidence: 97%
“…The equations used ( Equations (S1) and (S2) ), resulting doses ( Table S1 ) for simulations and the simulated concentration versus time profile ( Figures S2 and S3 ) are presented in the Supplementary Materials . The regimens tested in the simulations were based on those reported in the literature for treating fungal infections: recommended dose—initial dose of 6 mg/kg/12 h of VRC on the first day and maintenance dose of 4 mg/kg/12 h on each subsequent day—and a dosing regimen with a 50% reduced dose—initial dose of 3 mg/kg/12 h of VRC on the first day and maintenance dose of 2 mg/kg/12 h on each subsequent day (recommended for liver cirrhosis Child–Pugh A and B) [ 8 , 32 ]. First, we estimated the cerebrospinal fluid (CSF)-to-plasma unbound concentration ratio (K p,uu,CSF ) for rats by the simulation of 1000 individuals of the dataset randomly distributed.…”
Section: Methodsmentioning
confidence: 99%
“…Our study has the following limitations. The sample size included only 9 patients per groups, but this is a typical number of patients in PK studies [ 9 , 10 , 33 , 34 ]. We did not systematically evaluate thrombocytopenia or lactic acidosis as common adverse effects of linezolid because both findings are typical in the included population of critically ill patients, which prevents correct causal attribution.…”
Section: Discussionmentioning
confidence: 99%
“…RRT was performed as continuous veno-venous hemodialysis (CVVHD) or as a postdilution continuous veno-venous hemofiltration (CVVH) as described before [ 9 ]. Both methods were performed with Multifiltrate pro ® dialysis machines using an Ultraflux ® AV1000S hollow-fiber hemofilter (Fresenius Medical Care, Bad Homburg, Germany) with a membrane surface area of 1.8 m 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, although the overall PK of voriconazole is considered to be virtually unaffected by any mode of renal replacement therapy [ 32 , 33 ], one previous study indicated that continuous veno-venous hemofiltration (CVVH) with an ultrafiltration rate of 35 mL/(kg·h) may affect voriconazole clearance [ 34 ]. Some experts doubt whether even small amounts of voriconazole can be adsorbed onto the hemofilter membrane in the same way as onto the ECMO membrane; however, no relevant research has confirmed this hypothesis [ 35 ].…”
Section: Introductionmentioning
confidence: 99%